Good times bad times — Unfavorable breeding conditions, more than divorce, lead to increased parental effort and reduced physiological condition of northern gannets - Pelletier, David; Blier, Pierre; Vézina, François; Guillemette, Magella (Frontiers in Ecology and Evolution, 2023)
Decreased productivity in long-lived bird species is linked to prey depletion in marine ecosystems. Seabirds, however, exhibit behavioral flexibility at individual level to prevent this outcome. One such strategy to alleviate any impact on fitness would be to divorce from their partners. Although changing mates and increasing foraging effort have been shown to increase or maintain reproductive success, how the behavioral flexibility affects fundamental physiological parameters remains to be elucidated. Here, we compared physiological components (nutritional status, muscle damage and oxidative stress) of northern gannets (Morus bassanus) in relation to their partnership status and foraging effort. Specifically, we used a cross-sectional data set (at the population level) of three contrasted years to compare retained and changed mates. We predicted that mate change is a stressful event with impacts on health condition and those effects are higher during unfavorable years with food depletion. Our study showed that gannets changing mate increase parental effort only during years of low food abundance, with consequences on health condition (increased body mass loss, higher protein catabolism and higher oxidative damage during chick rearing period). Ultimately, our study suggests that partnership decision is not likely to reduce the long-term quality and the fitness of parents. Reproduction during harsh conditions would however likely be one of the primary causes of individual quality loss and fitness decline in this long-lived bird species.